The Power of Story in an Animation Industry - Kadek Satria Adidharma (Bina Nusantara University, 2011)
After the founding of the Walt Disney Company, animation becomes something necessary in our everyday life. The real power why the animation bigger is the storytelling. Story is the main key why animation is loveable by audiences. This writing will be focusing on the behind reason why the story is important in animation and will be giving some examples the success story of some animation which have a great story to tell. The design methodology focuses on data research, market research and literature book. This writing is a preliminary research because from the author concern, there are not many writings debating whether which part in the development will be focused on to developing some animation projects. This writing hopefully will help people who want to build some animation projects and will guide them to make decision because in order to build some animation project there will be a massive effort to be conducted. Hopefully, in the future, there will be more animation produced from Indonesian. To be an unforgettable work, it must have a great story.